Seconds - Goldsmith, Jerry 1929-2004 (Eureka Entertainment, 2015)
"[...] John Frankenheimer directs Rock Hudson as a second : that is, the newly plastic-surgery altered reboot of, in this instance, a listless banker named Arthur Hamilton. Such procedures are carried out by a secret organization known only as The Company, with the promise of giving an individual a chance at making a fresh start at life... but at what cost? Master lighting cameraman James Wong Howe provides the paranoiac atmosphere to the skewed reality of what came to be widely considered one of Frankenheimer s very best films. [...]" [amazon.de]
Original: USA 1966
Bonus: feature-length audio commentary with director John Frankenheimer ; feature-length audio commentary with film scholar Adrian Martin ; new video interview with novelist and critic Kim Newman ; booklet featuring new essays by critics David Cairns and Mike Sutton
Keywords: DVD-Video; Blu-Ray-Disc